Clinicopathological and immunohistochemical evaluation of oesophageal leiomyosarcoma in a dog - Alves, Renata Cintra Ciccone; Batista, Tatiana Linardi; Laufer-Amorim, Renée [UNESP]; Elias, Fabiana; Calazans, Sabryna Gouveia; Fonseca-alves, Carlos Eduardo [UNESP] (Universidade Federal de Santa Maria, 2015)
Oesophageal leiomyosarcoma is a malignant neoplasm of smooth muscle fibres that is infrequently reported in the literature. Because of the importance of definitive diagnosis and the low incidence of this tumour in dogs, it was reported a case of oesophageal leiomyosarcoma in a dog. A 13-year-old intact male Rottweiler presented regurgitation, hyporexia, and chronic weight loss. After an imaging examination, tumour in the thoracic oesophagus was suspected and a biopsy was sugested for definitive diagnosis. However, the owner did not permit the procedure. Six months after the clinical diagnosis, the patient was brought for evaluation of anorexia, apathy, and severe dyspnoea. Because of the patient's clinical signs and lack of response to emergency treatment, he was euthanized. Upon necropsy, it was identified the neoplastic formation, previously identified in the radiographic examination in the thoracic oesophagus, near the diaphragm. Histopathology revealed a proliferation of mesenchymal cells, and the diagnosis of leiomyosarcoma was confirmed by immunohistochemical examination. Despite the low incidence of oesophageal leiomyosarcoma, it should be included as a differential diagnosis for animals with chronic regurgitation.

O leiomiossarcoma esofágico é um neoplasma maligno das fibras musculares lisas pouco descrito na literatura e, devido à importância do seu diagnóstico definitivo e à baixa frequência desta neoplasia em cães, relata-se um caso de leiomiossarcoma em localização esofágica. Foi atendido um cão, 13 anos, Rottweiler, com histórico de regurgitação, hiporexia e perda de peso crônica. Após exames complementares de imagem, suspeitou-se de neoplasma localizado em esôfago torácico, no entanto, o proprietário optou por não realizar nenhum exame para o diagnóstico definitivo. Após seis meses do atendimento inicial, o animal retornou com anorexia, apatia e dispneia severa. Devido aos sinais clínicos apresentados e ausência de resposta ao tratamento emergencial instituído, optou-se pela eutanásia. Foi realizada a necropsia e, no esôfago torácico, próximo à região diafragmática, foi possível identificar a formação neoplásica anteriormente visualizada no exame radiográfico. O exame histopatológico revelou proliferação de células mesenquimais, sugestiva de leiomiossarcoma. O diagnóstico foi confirmado pelo exame imuno-histoquímico. Apesar da baixa frequência do leiomiossarcoma esofágico, animais que apresentam regurgitação crônica devem ser investigados quanto à possibilidade desse diagnóstico.
Aspectos clínico-patológicos e imuno-histoquímicos de um caso de leiomiossarcoma esofágico canino
Keywords: Diseases of dogs; Esophagus; Neoplasms; Smooth muscle; Doenças de cães; Esôfago; Neoplasias; Músculo liso